If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -3)(8x + 4) = 0 Reorder the terms: (-3 + 4x)(8x + 4) = 0 Reorder the terms: (-3 + 4x)(4 + 8x) = 0 Multiply (-3 + 4x) * (4 + 8x) (-3(4 + 8x) + 4x * (4 + 8x)) = 0 ((4 * -3 + 8x * -3) + 4x * (4 + 8x)) = 0 ((-12 + -24x) + 4x * (4 + 8x)) = 0 (-12 + -24x + (4 * 4x + 8x * 4x)) = 0 (-12 + -24x + (16x + 32x2)) = 0 Combine like terms: -24x + 16x = -8x (-12 + -8x + 32x2) = 0 Solving -12 + -8x + 32x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-3 + -2x + 8x2) = 0 Factor a trinomial. 4((-1 + -2x)(3 + -4x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-1 + -2x)' equal to zero and attempt to solve: Simplifying -1 + -2x = 0 Solving -1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2x = 0 + 1 -2x = 0 + 1 Combine like terms: 0 + 1 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5Subproblem 2
Set the factor '(3 + -4x)' equal to zero and attempt to solve: Simplifying 3 + -4x = 0 Solving 3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = 0 + -3 -4x = 0 + -3 Combine like terms: 0 + -3 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75Solution
x = {-0.5, 0.75}
| 3(x+2)+3x+1=2(x-1)-7 | | 11/28=4/x | | 12x^3-3x^2=0 | | 3.5/x=11/28 | | 55x-12=x-24 | | 59+1.75x=39.99+2.50x | | x(1M)+(-2N)=0 | | 2/3x2-5= | | 3p+6=78 | | 2/3x-5=-2 | | C(t)=2x+180 | | 5x-5y+7a= | | 3=-3/2(x+6) | | Ic(t)=2x+180 | | 16=4(2x+1) | | x-1/2=1/4 | | y^1/7 | | -9=x+20 | | 14=s-61 | | k/-4=3 | | q+5=8(q+7) | | -20=-2+3v | | 6a^2+4a=-11 | | 25-6x=19-5x | | 6m^2+13=5 | | .05x/259y=5550 | | .05x*259y=5550 | | 4x+28=10 | | 18=4w+2 | | .40x+1.25y=150 | | sinx+-1cosx+-1tanx=-1 | | 3y+4x-Y-2x-5y= |